ACTUAL PROBLEMS IN STUDYING THE KAZAKH SHEZHERE - Izatulla, Habibian; Turgunbayev, Y.; Nurkina, A. (Journal of history, 2018)
In the article the author affected in actual problems in the field of genealogy. The attitude of the Kazakhs to shezhere is sacred. Many modern Kazakhs are trying to recover their roots and learn their ancestry. The article describes the specific results of the study shezhere of Kazakhs, investigated by the author as a genealogical memory and historical source, as a cultural tradition and original forms of historical knowledge of the Kazakh people. In this article, shezhere represented as a set of historical and genealogical materials, which was used to study the law, tribal life and ethnic composition of the population of the steppe. The concept of “shezhere” means “family tree”, “memory”, “genealogy”. In this article, the author describes a shezhere how the document, containing the most diverse historical information, which includes, primarily, folk genealogy.